2021
DOI: 10.1039/d1cc03186d
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic ethylbenzene valorization using a polyoxometalate@covalent triazine framework with water as the oxygen source

Abstract: Ethylbenzene (EB) oxidation is an important transformation in chemical industry. Herein, PMo10V2@CTF, a noble metal free electrocatalyst, was used to promote the oxidative upgrading of EB. Under ambient conditions, 65%...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It is worth noting that the sulfenamides rubber vulcanization accelerators in solid phase and H 2 in gas phase in the indirect electrocatalytic systems can be readily separated and collected, resulting in simultaneous generation of varied value‐added products in a single system. [ 44,49 ] This powerful system that can simultaneous production of value‐added chemical products and H 2 hold much potential in practical industrial applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the sulfenamides rubber vulcanization accelerators in solid phase and H 2 in gas phase in the indirect electrocatalytic systems can be readily separated and collected, resulting in simultaneous generation of varied value‐added products in a single system. [ 44,49 ] This powerful system that can simultaneous production of value‐added chemical products and H 2 hold much potential in practical industrial applications.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the sulfenamides rubber vulcanization accelerators in solid phase and H 2 in gas phase in the indirect electrocatalytic systems can be readily separated and collected, resulting in simultaneous generation of varied value-added products in a single system. [44,49] This powerful system that can simultaneous production of value-added chemical products and H 2 hold much potential in practical dustrial applications. Furthermore, in order to further explore the properties of the sulfenamides rubber additives, we have successfully applied thus-obtained sulfenamides rubber additives (1c and 2c) in the rubber vulcanization industry applications (Figure S23a-d, Supporting Information).…”
Section: Electrocatalytic Property Of Pw 10 Cu 2 @Cmcmentioning
confidence: 99%
See 1 more Smart Citation
“…or small molecules (H 2 O, O 2 , etc.). [17][18][19][20][21] For instance, Sargent et al 17 reported Cl À -mediated oxidation of ethylene to ethylene oxide with high selectivity, which achieved a current density of 1 A cm À2 and a faradaic efficiency of B70%. Qian et al 18 demonstrated that bromine and oxygen redox species promote the highly selective electro-epoxidation of ST. With this advance as an inspiration, the electrooxidation of ST to form BzH might be realized by utilizing a reaction mediated by reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…Polyoxometalates, as typical Brønsted acids, have also been applied in the Ritter reaction. [16][17][18][19] For instance, Firouzabadi et al showed that H 3 PW 12 O 40 can efficiently catalyze the amidation of various alcohols with nitriles under reflux conditions. 17 However, for the reaction of solid nitriles, additional sodium dodecyl sulfate was required.…”
mentioning
confidence: 99%